وساطات دولة قطر خارج المنطقة العربية في الفترة ما بين 2005-2015 : دراسة تحليلية في أبعاد العلاقات الدولية - مناعي، عيسى بن محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study deals with the mediation of the State of Qatar beyond the Arab region: an analytical study in the dimensions of international relations. This is a very important area that has yet to be researched as it conceptualizes the case of mediations with non-Arabs as well as non-Muslims besides its visible humanitarian aspect. This research relies on four perspectives: firstly, it deals with human perspective in terms of the human feeling towards his fellow man, regardless of gender, nationality, color, or religion. Secondly, it also relies on the Arab heritage that was inherited from fathers and grandfathers, mainly customs and traditions as well as the customs of defining the “stranger” and the “wayfare” and the “outsider”. Thirdly and most essentially, it includes the legitimate aspect which denounces injustice, harm or damage as per Islamic legislation and its script in dealing with warriors, Dhimmis, adherents and believers as well as those of power. This is - in light of the fairly Islamic state where no one is bound. The fourth perspective is the diplomatic approach in the foreign policy of the State of Qatar, in which the language of dialogue and communication within the framework of settlement and peaceful solutions between the conflicting parties are adopted. Recently, the State of Qatar has recorded huge achievements, in record time successfully conducted humanitarian mediations of civilian and military hostages, which were the most complex and linked to hot conflicts and disputes regionally and globally. This research historically documents the different types of medium identified by the researcher in terms of time and place. As it is presented, for the first time, in an academic form (not through media and politics), this research is an achievement in the contemporary international mediation field. As 80% of mediations depend on verbal communication and 20% tend to document the writing of mediations, the researcher used four approaches to examine this topic. The four approaches are: the desk approach (inductive), the historical approach (descriptive), the analytical approach (discussion), and the critical approach (objective) as they are the most appropriate for this study.